The growth performance of different commercially important rattans at eight years after planting - C. RENUKA, P. RUGMINI, J. P. THOMAS and V. V. RANGAN (J. Bamboo and Rattan, Vol. 3, No. 3, pp. 187-193 (2004), 2004)
A species trial with eight commercially important rattan species was conducted at two different elevations in the natural forests in Kerala. When both survival and total height are considered, Calamus baratangensis is the best species suited for areas around 1000 m elevation and Daemonorops kurzianus for 300 m. In the 6th year C. baratangensis produced 18 m of commercially utilizable cane at 1000 m and 45 m at 300 m. But during the 8th year the survival percentage of this species was reduced to 10 per cent at 300 m. At the end of 6th year four species reached a harvestable length at 1000 m and five species reached a harvestable length at 300 m.